Annexin A1 Bioactive Peptide Promotes Resolution of Neuroinflammation in a Rat Model of Exsanguinating Cardiac Arrest Treated by Emergency Preservation and Resuscitation - Ma, Qing; Zhang, Zhiquan; Shim, Jae-Kwang; Venkatraman, Talaignair N.; Lascola, Christopher D.; Quinones, Quintin J.; Mathew, Joseph P.; Terrando, Niccolò; Podgoreanu, Mihai V. (Frontiers in Neuroscience, 2019)
Neuroinflammation initiated by damage-associated molecular patterns, including high mobility group box 1 protein (HMGB1), has been implicated in adverse neurological outcomes following lethal hemorrhagic shock and polytrauma. Emergency preservation and resuscitation (EPR) is a novel method of resuscitation for victims of exsanguinating cardiac arrest, shown in preclinical studies to improve survival with acceptable neurological recovery. Sirtuin 3 (SIRT3), the primary mitochondrial deacetylase, has emerged as a key regulator of metabolic and energy stress response pathways in the brain and a pharmacological target to induce a neuronal pro-survival phenotype. This study aims to examine whether systemic administration of an Annexin-A1 bioactive peptide (ANXA1sp) could resolve neuroinflammation and induce sirtuin-3 regulated cytoprotective pathways in a novel rat model of exsanguinating cardiac arrest and EPR. Adult male rats underwent hemorrhagic shock and ventricular fibrillation, induction of profound hypothermia, followed by resuscitation and rewarming using cardiopulmonary bypass (EPR). Animals randomly received ANXA1sp (3 mg/kg, in divided doses) or vehicle. Neuroinflammation (HMGB1, TNFα, IL-6, and IL-10 levels), cerebral cell death (TUNEL, caspase-3, pro and antiapoptotic protein levels), and neurologic scores were assessed to evaluate the inflammation resolving effects of ANXA1sp following EPR. Furthermore, western blot analysis and immunohistochemistry were used to interrogate the mechanisms involved. Compared to vehicle controls, ANXA1sp effectively reduced expression of cerebral HMGB1, IL-6, and TNFα and increased IL-10 expression, which were associated with improved neurological scores. ANXA1sp reversed EPR-induced increases in expression of proapoptotic protein Bax and reduction in antiapoptotic protein Bcl-2, with a corresponding decrease in cerebral levels of cleaved caspase-3. Furthermore, ANXA1sp induced autophagic flux (increased LC3II and reduced p62 expression) in the brain. Mechanistically, these findings were accompanied by upregulation of the mitochondrial protein deacetylase Sirtuin-3, and its downstream targets FOXO3a and MnSOD in ANXA1sp-treated animals. Our data provide new evidence that engaging pro-resolving pharmacological strategies such as Annexin-A1 biomimetic peptides can effectively attenuate neuroinflammation and enhance the neuroprotective effects of EPR after exsanguinating cardiac arrest.